2013
DOI: 10.1260/1747-9541.8.2.395
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Kinematics during the Take-Off Phase in Competitive Long Jumping

Abstract: The purpose of the present study was to identify the relationships among selected kinematic variables that affect the take-off phase and performance in elite jumpers. The jump distance was found to be related to: I) the athlete's approach speed before the instant of touch down; and ii) the exchange in spatial velocity components at take-off, which results in a gain in maximum vertical velocity of the centre of mass (CM), favoured by the use of an optimum touch-down angle of the take-off leg, an active landing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
13
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 18 publications
6
13
2
Order By: Relevance
“…Furthermore, non-amputee athletes from the present study did not reach peak hip flexion prior to 25 ± 1.7% of the stance phase, and then reached maximum extension of the hip at TO with values similar to those in [19,20] but about 12° greater compared to those in [15]. This discontinuous sagittal plane hip motion contrasts with previous studies that reported continuous hip extension throughout ground contact [19,20]. These differences between studies, especially during the early stance phase of the take-off step, might be due to a shorter average jump distance in our study or due to lower sampling rates (100 or 125 Hz) [15,19,20] and lower cut-off frequencies (8 or 8.3 Hz) [15,19] used in previous studies.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Furthermore, non-amputee athletes from the present study did not reach peak hip flexion prior to 25 ± 1.7% of the stance phase, and then reached maximum extension of the hip at TO with values similar to those in [19,20] but about 12° greater compared to those in [15]. This discontinuous sagittal plane hip motion contrasts with previous studies that reported continuous hip extension throughout ground contact [19,20]. These differences between studies, especially during the early stance phase of the take-off step, might be due to a shorter average jump distance in our study or due to lower sampling rates (100 or 125 Hz) [15,19,20] and lower cut-off frequencies (8 or 8.3 Hz) [15,19] used in previous studies.…”
Section: Discussionsupporting
confidence: 71%
“…The vertical COM movement of the non-amputee athletes from the current study is in agreement with the results of Lees et al . [15], but vertical COM increase during the take-off step was about 7–8 cm lower than reported in other studies [19,20]. Based on the conflicting ideas mentioned above and a previous discussion by Hay et al .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Only a weak correlation between this measurement and ED was exhibited in Group B, along with a very weak correlation in Group A (Table 2) (the differences between correlation coefficients in Groups B and A were non-significant, p = 0.211). At the same time, Campos et al (2013) found medium significant relationships between ED and relative center of mass height at takeoff (r = 0.577; p < 0.001) in the group of eight male finalists of the IAAF World Indoor Championships Valencia 2008.…”
Section: Discussionmentioning
confidence: 84%
“…A non-significant relationship between approach velocity and effective distance (r = 0.496, P > 0.05) was observed, for example, by Graham-Smith and Lees (2005) among the participants of AAA Championships in the UK (ED from 7.17 to 7.84 m). Graham-Smith and Lees (2005) (as well as Campos et al (2013)) also found only a weak correlation between ED and horizontal (r = 0.215, P > 0.05 (Graham-Smith & Lees, 2005) and r = -0.231, p < 0.189 (Campos, et al, 2013) and vertical (r = 0.279, P > 0.05 (Graham-Smith & Lees, 2005) and r = 0.454, p < 0.01 (Campos, et al, 2013)) takeoff velocities, and no correlation between ED and center of mass height at takeoff (which are important in the long jump according to the model of Hay et al (1986)). Graham-Smith and Lees (2005) explained this by the variability in relation to the range for each variable.…”
Section: Discussionmentioning
confidence: 99%